MULTIDIMENSIONALITY OF SOCIAL RELATIONS - Мокляк, Н. Н.; Мокляк, Л. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the analysis of multidimensionality of social relations in the frame of the multidimensional structure of society from one point of view and the multidimensional structure of personality from another.